De-jittering Ariel: An optimized algorithm - Bocchieri, Andrea; Mugnai, Lorenzo V.; Pascale, Enzo; Papageorgiou, Andreas; Syty, Angèle; Tsiaras, Angelos; Eccleston, Paul; Savini, Giorgio; Tinetti, Giovanna; Broquet, Renaud; Chapman, Patrick; Sechi, Gianfranco (Experimental astronomy, 2025)
The European Space Agency’s Ariel mission, scheduled for launch in 2029, aims to conduct the first large-scale survey of atmospheric spectra of transiting exoplanets. Ariel achieves the high photometric stability on transit timescales required to detect the spectroscopic signatures of chemical elements with a payload design optimized for transit photometry that either eliminates known systematics or allows for their removal during data processing without significantly degrading or biasing the detection. Jitter in the spacecraft’s line of sight is a source of disturbance when measuring the spectra of exoplanet atmospheres. We describe an improved algorithm for de-jittering Ariel observations simulated in the time domain. We opt for an approach based on the spatial information on the Point Spread Function (PSF) distortion from jitter to detrend the optical signals. The jitter model is based on representative simulations from Airbus Defence and Space, the prime contractor for the Ariel service module. We investigate the precision and biases of the retrieved atmospheric spectra from the jitter-detrended observations. At long wavelengths, the photometric stability of the Ariel spectrometer is already dominated by photon noise. Our algorithm effectively de-jitters both photometric and spectroscopic data, ensuring that the performance remains photon noise-limited across the entire Ariel spectrum, fully compliant with mission requirements. This work contributes to the development of the data reduction pipeline for Ariel , aligning with its scientific goals, and may also benefit other astronomical telescopes and instrumentation.